Serum NfL levels in the first five years predict 10-year thalamic fraction in patients with MS. Issue 1 (January 2022) - Lokhande, Hrishikesh; Rosso, Mattia; Tauhid, Shahamat; Chu, Renxin; Healy, Brian C.; Saxena, Shrishti; Barro, Christian; Paul, Anu; Polgar-Turcsanyi, Mariann; Anderson, Mark; Glanz, Bonnie I.; Kropshofer, Harald; et al.
Background: Serum neurofilament light chain (sNfL) levels are associated with relapses, MRI lesions, and brain volume in multiple sclerosis (MS). Objective: To explore the value of early serum neurofilament light (sNfL) measures in prognosticating 10-year regional brain volumes in MS. Methods: Patients with MS enrolled in the Comprehensive Longitudinal Investigations in MS at Brigham and Women's Hospital (CLIMB) study within five years of disease onset who had annual blood samples from years 1–10 (n = 91) were studied. sNfL was measured with a single molecule array (SIMOA) assay. We quantified global cortical thickness and normalized deep gray matter (DGM) volumes (fractions of the thalamus, caudate, putamen, and globus pallidus) from high-resolution 3 T MRI at 10 years. Correlations between yearly sNfL levels and 10-year MRI outcomes were assessed using linear regression models. Results: sNfL levels from years 1 and 2 were associated with 10-year thalamus fraction. Early sNfL levels were not associated with 10-year putamen, globus pallidus or caudate fractions. At 10 years, cortical thickness was not associated with early sNfL levels, but was weakly correlated with total DGM fraction. Conclusions: Early sNfL levels correlate with 10-year thalamic volume, supporting its role as a prognostic biomarker in MS.